Envisaging Beyond Community-Based Health Insurance in Nepal - Magar, A (Journal of Nepal Health Research Council, 2014)
Every nation in the world, wish to provide all health care free  of  cost  to  its  citizens,  if  not  easily  accessible  and more affordable. But all of them have limited resources in  terms  of  infrastructure,  health  workforce  and  most importantly  the  financing.  The health financing is one of the six building blocks of a health system, which play crucial role for improving health of a country.